PLATO’S PHILOSOPHY OF POLITICAL EDUCATION AS A WAY FOR CANDIDATES FOR INDONESIAN LEADERS - Siti Umroh (Jurnal Cakrawala Ilmiah, 2022)
This study aims to review the formulation of an educational program to prepare prospective leaders with Plato's political philosophy of education in the midst of the problems of learning in Indonesia which is limited to rote practice so that it pays less attention to students' reasoning. Especially in this democratic regime, students lack moral role models because many state officials commit corruption. The type of research used in this research is descriptive qualitative with the type of literature study (library research), so that the source of the data obtained comes from the text. Data sources are divided into two, namely primary data and secondary data. Primary data is The Republic Plato, while secondary data includes books, journals, magazines, mass media, and articles relevant to the title of the discussion. Data from various sources will be processed analytically descriptively regarding Plato's political education philosophy, then integrated with the 2013 curriculum, then conclusions are drawn. The result of this research is that the main target of Plato's philosophy of political education is the soul, so the educational program (paideia) to prepare future leaders implies an artificial (mimesis, imitation) obtained through mousike and gymnastics to direct thumos. The soul always follows what is directed. Mousike, gymnastics, and dialectics are a paidia (game) which is a combination in the educational process.